Wear resistance of cast irons used in brake disc rotors - Cueva G. (2003)
The wear resistance of three different types of gray cast iron (gray iron grade 250, high-carbon gray iron and titanium alloyed gray iron), used in brake disc rotors, was studied and compared with the results obtained with a compact graphite iron (CGI). The wear tests were carried out in a pin-on-disc wear-testing machine, the pin being manufactured from friction material usually used in light truck brake pads. The rotating discs (500 rpm) were subjected to cyclical pressures of 0.7, 2 and 4 MPa and forced cooled.The wear was measured by weighing discs and pads before and after the test. The operating temperatures and friction forces were also monitored during each test. The results showed that compact graphite iron reached higher maximum temperatures and friction forces as well as greater mass losses than the three gray irons at any pressure applied. However, when compact graphite iron was tested with lower applied pressures and same friction forces sustained by the gray iron rotors, CGI presented the same performance, as did the gray cast iron. © 2003 Elsevier Science B.V. All rights reserved.